مراعاة مصلحة المحضون بين مقتضيات الأحكام الفقهية والممارسة القضائية - بجاق, محمد (University of Eloued جامعة الوادي, 2014)
إن حضانة الطفل واجبة ما دام الولد في أمس الحاجة إلى الرعاية والعناية، حيث يكون عاجزا عن مباشرة مصالحه بنفسه، ولا يميز بين ما يضره أو ينفعه. وتقتضي المصلحة الاجتماعية حماية الطفل وتقرير أحكام متماشية ومصلحته؛ ولهذا حرصت الشريعة الإسلامية وكذا القوانين المختلفة على وضع الشروط والضوابط التي تضمن حماية مصلحة الطفل المحضون، وعلى ضوء تلك الأحكام جاءت الممارسات القضائية. وفي هذه الصفحات تبيان لأحكام مراعاة مصلحة المحضون نظرية وتطبيقا من خلال ثلاثة مباحث؛ تطرق الأول إلى تعريف الحضانة، مشروعيتها، وتكييفها الفقهي؛ وبحث الثاني في مصلحة المحضون، مفهومها، خصائصها، وتقديرها. أما الثالث فخصص لعرض تطبيقات قاعدة مراعاة مصلحة المحضون في الفقه والقضاء. Child custody is obligatory as long as the boy in urgent need of care and attention, where he is unable to direct his own interests, and he does not distinguish between what harm him or help him. Islamic law has been keen as well as the various laws to establish the conditions and controls that ensure the protection of the interests of the child custody, judicial practices came in the light of those provisions. This research shows the provisions of the child taking into account interest of the child custody through three sections. The first relates to the definition of custody, and its legitimacy. The second related to interests of the child custody, its concept, its characteristics, and its appreciation. The third is related to the applications of the base taking into account interests of the child in jurisprudence and judicial practice.
مقال بمجلة البحوث والدراسات
Keywords: الحضانة- المصلحة- الأسرة- الرعاية- الطفل- القضاء; custody - interest - the family - care - the child - the judiciary